Service Excellent For Islamic Micro Financial Institution During Covid-19 Pandemic - Trimulato Trimulato; Muhlis Muhlis; Farid Fajrin; Supriadi Hamid; Trisno Wardy Putra (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2021)
The development of Islamic financial institutions in Indonesia continues to increase. But, the development of Islamic finance institutions is hindered due to the impact of the Covid-19 outbreak. In particular, Islamic non-bank financial institutions include Islamic microfinance institutions (IMFI). SMEs that become the market segment of IMFI are affected by the Covid-19. Amid this condition, IMFI still has survived and developed and provides excellent service to customers. This study aims to determine the development of IMFI and to know the pattern of service excellence for IMFI in the condition of the Covid-19 outbreak. This research is qualitative and uses library research. Data sources obtained from several sources are considered relevant themes, especially sources of certain institutions that provide data relating to the development of IMFI. The data analysis technique used is a qualitative descriptive overview of the development of IMFI and service excellent pattern for amid the Covid-19 outbreak. Results showed the growth of IMFI in March 2021, whose assets experienced growth of 6.8 percent and financing growth of 13.66 percent. IMFI can do the excellent service pattern amid the Covid-19 outbreak, continues services as usually by following existing rules, increasing intensity of communication with customers, cooperating with other Islamic financial institutions, and improving service indirectly giving customers access.